2022
DOI: 10.1093/gji/ggac392
|View full text |Cite
|
Sign up to set email alerts
|

Using teleseismic backprojection and InSAR to obtain segmentation information for large earthquakes: a case study of the 2016Mw 6.6 Muji earthquake

Abstract: Summary A good understanding of earthquake rupture segmentation is important to characterize fault geometries at depth for follow-up tectonic, stress-field or other analyses. We propose a data-driven strategy and develop pre-optimization methods to support finite fault inversions with independent prior estimates on earthquake source parameters. The first method we develop is a time-domain, multi-array and novel multi-phase backprojection of teleseismic data. This method infers the spatio-tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The simple kinematic model used to calculate the synthetics produces sharper start and stop phases than actually observed (Steinberg et al, 2022), as the modelled fault ends abruptly, whereas in nature there would be tapering. Furthermore, the synthetic semblance maps produce much sharper semblance patches in comparison to the real data backprojection.…”
Section: Implications From Back-projectionmentioning
confidence: 92%
See 4 more Smart Citations
“…The simple kinematic model used to calculate the synthetics produces sharper start and stop phases than actually observed (Steinberg et al, 2022), as the modelled fault ends abruptly, whereas in nature there would be tapering. Furthermore, the synthetic semblance maps produce much sharper semblance patches in comparison to the real data backprojection.…”
Section: Implications From Back-projectionmentioning
confidence: 92%
“…Therefore, a mismapping of this semblance seems likely. Previous studies have shown that the choice of grid depth and the deviation of the source depth from the grid depth have a strong effect on the location of the mapped semblance (Steinberg et al, 2022;Daout et al, 2020), so this seems to be the likely cause. However, waveform coda and depth phases can also contaminate the BP results, especially in the later stages of the rupture process.…”
Section: Implications From Back-projectionmentioning
confidence: 96%
See 3 more Smart Citations